1990
DOI: 10.1530/jrf.0.0890579
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of fibronectin by rat granulosa cells occurs primarily during early follicular development

Abstract: Rats were pretreated with oestradiol-17 beta or PMSG, treatments producing mainly preantral and antral follicles respectively. The granulosa cells from these two treatments, E2- and PMSG-cells respectively, were cultured for 2 successive 24-h periods. Basal progesterone secretion, stimulated 3- to 5-fold by FSH, was almost 8-fold higher by PMSG-cells than by E2-cells at 24 and 48 h. Similarly, PMSG-cells secreted 16-fold more 20 alpha-dihydroprogesterone than did E2-cells, in the absence of FSH, and 6- to 10-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Both FSH and insulin decrease, whereas GnRH increases, fibronectin production from rodent granulosa cells. In addition, granulosa cells from preantral follicles secrete considerably larger amounts of fibronectin than granulosa cells from antral follicles [18].…”
Section: Discussionmentioning
confidence: 94%
“…Both FSH and insulin decrease, whereas GnRH increases, fibronectin production from rodent granulosa cells. In addition, granulosa cells from preantral follicles secrete considerably larger amounts of fibronectin than granulosa cells from antral follicles [18].…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have demonstrated the presence of fibronectin in the follicle layers of ovarian follicles in mammals [34][35][36][37][38], as well as in teleost fish [39]. Fibronectin is presumed to stabilize and maintain the ECM environment and normal cell adhesion by interacting with collagen type IV and the cell surface receptor protein integrin [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…All procedures were performed at room temperature. The cells were first fixed (5 min) with 3.7% paraformaldehyde in PBS and then permeabilized (20 min) with 0.1% PBS-Nonidet P-40 [25,26]. The cells were rinsed with PBS and then incubated (45 min) with a specific antiserum to laminin or collagen IV (rabbit anti-mouse; Collaborative Research) or to fibronectin (goat anti-human; Terochem Laboratories, Toronto, ON).…”
Section: Immunolocalization Of Extracellular Matrix Glycoproteinsmentioning
confidence: 99%